Perbedaan Skor Anxiety antar User Konseling Online dengan Non-User Konseling Online di Sumatera Barat - Khair, Nurul Fadhilah; Reza, Faisal Adnan; Farid, Risanita Fardian (Universitas Islam Negeri Raden Intan Lampung, 2021)
Online counseling, or cyber counseling, or virtual counseling, is one of the new trends that has emerged since the COVID-19 pandemic. This trend is attached to teenagers aged 17 to 19 years who currently sit in college on average. Living side by side with technology, it is easy for them to keep up with these new developments. However, whether online counseling services, or cyber counseling, or virtual counseling, are able to reduce the most common anxiety symptoms that arise in individual mental health disorders. This type of research is a survey, which involves 172 students from XY University, West Sumatra which are divided into user and non-user groups of online counseling. Descriptive statistical analysis technique was used to see the difference in scores between the two groups. The results showed that the anxiety level in the online counseling user group was higher than the non-user group.Keywords: online counseling, anxiety scores, adolescents